Efektivitas dan Faktor Penentu Skema Perdamaian dalam Penyelesaian Kepailitan: Analisis Kasus No. 10/Pdt.Sus-PKPU/2018/PN.Niaga.Mks - Natsir, Muthmainnah; Husen, La Ode (CV. Social Politic Genius (SIGn), 2024)
This research aims to analyze the efficacy of bankruptcy resolution achieved through composition schemes within the Makassar Commercial Court, along with the determinants affecting such efficacy. Employing a qualitative descriptive approach, this study integrates normative and empirical legal research methodologies. The research was conducted at the Makassar Class IA District Court. Data collection techniques involved interviews, documentation review, and literature review. Collected data were analyzed using qualitative data analysis techniques. Findings reveal that bankruptcy cases within the Makassar Commercial Court are predominantly resolved via composition schemes. This method is perceived as highly effective, and its process is consistent with Law Number 37 of 2004. The role of the curator, under the supervision of the supervisory judge, facilitates the reaching of agreements between debtors and creditors to resolve their debts relatively quickly, at a lower cost, and through a process perceived as less complex. However, several determinants act as constraints, negatively impacting resolution via composition, including varying educational levels among stakeholders, limited understanding of Law Number 37 of 2004, the heavy caseload often managed by individual curators, and the prevalence of a ‘gengsi’ (prestige-saving) culture. Therefore, public legal education and awareness initiatives are necessary, particularly targeting the business community, to enhance legal awareness and comprehension concerning the process and potential efficacy of bankruptcy resolution through composition within the Makassar Commercial Court, pursuant to Law Number 37 of 2004. Furthermore, in light of potentially increasing bankruptcy filings, the Makassar Commercial Court should consider increasing the number of appointed curators to facilitate more efficient and timely case resolution.